Prospective, randomised controlled trial comparing Versajet™ hydrosurgery and conventional debridement of partial thickness paediatric burns. Issue 4 (June 2015) - Hyland, Ela J.; D'Cruz, Rachel; Menon, Seema; Chan, Queenie; Harvey, John G.; Lawrence, Torey; La Hei, Erik; Holland, Andrew J.A.
Highlights Versajet™ in children would seem an effective means of burn wound debridement. Versajet™ appears to be more precise method than conventional techniques. No differences appear in healing between Versajet™ or conventional techniques. Operating times using Versajet™ or conventional debridement were equivalent. No differences in scarring were found using Versajet™ or conventional debridement.